Neuroblastoma causes alterations of the intestinal microbiome, gut hormones, inflammatory cytokines, and bile acid composition. Issue 8 (11th January 2017) - Castellani, Christoph; Singer, Georg; Kaiser, Margarita; Kaiser, Thomas; Huang, Jianfeng; Sperl, Daniela; Kashofer, Karl; Fauler, Guenter; Guertl‐Lackner, Barbara; Höfler, Gerald; Till, Holger
Abstract: Objective: To assess the effect of neuroblastoma (NB) on the intestinal microbiome, metabolism, and inflammatory parameters in a murine model. Materials and Methods: Athymic Hsd:Fox1nu mice received subperitoneal implantation of human NB cells (MHH‐NB11) (tumor group, TG) or culture medium (sham group). Following 10 weeks of tumor growth, all animals were sacrificed to collect total white adipose tissue (WAT). Luminex assays were performed for gut hormone and inflammation marker analysis. Bile acids were measured by high‐performance liquid chromatography–mass spectrometry in feces and serum. The microbiome of the ileal content was determined by 16S rDNA next‐generation sequencing. Results: At 10 weeks, tumors masses in the TG reached a mean weight of 1.10 g (interquartile range 3.45 g) associated with a significant reduction in WAT. Furthermore, in the TG, there was a marked reduction in leptin and an increase in glucagon‐like peptide 1 serum levels. Moreover, the TG mice displayed a pro‐inflammatory profile, with significant increases in monocyte chemotactic protein 1, tumor necrosis factor alpha, and interleukin‐10. Lithocholic acid, deoxycholic acid, and ursodeoxycholic acid were significantly decreased in the stool of TG mice. Significant alterations of the intestinal microbiome were found in the ileal contents of the TG. Conclusions: The present study provides a first glimpse that human NB in a murine model induces tumor cachexia associated with alterations in metabolic and inflammatory parameters, as well as changes in the intestinal microbiota. Since the intestinal microbiome is known to contribute to the host's ability to harvest energy, a favorable modulation of the intestinal microbiome in tumor patients could potentially represent a novel therapeutic target to prevent tumor‐associated cachexia.